Novel Dual Two‐Dimensional Liquid Chromatography Online Coupled to Ultraviolet Detector, Fluorescence Detector, Ion‐Trap Mass Spectrometer for Short Peptide Amino Acid Sequence Determination with Bottom‐Up Strategy. Issue 6 (7th February 2018) - Cheng, Cheanyeh; Liao, Chien‐Fu
Abstract : A novel dual two‐dimensional (2D) high‐performance liquid chromatography (LC) setup coupled online to an ultraviolet (UV) detector, fluorescence (FL) detector, and ion‐trap mass spectrometer (MS) has been developed for determining the amino acid sequence of short peptides using a novel bottom‐up strategy. Short peptides were electrothermally hydrolyzed to shorter peptides and amino acid enantiomers. The first 2D LC‐UV and FL system was used to separate and identify the produced parent and daughter short peptides and amino acid isomers and enantiomers in the hydrolysate; the second 2D LC‐MS was used to identify the presence of cysteine and obtain the molecular mass signals and N‐terminal peptide fragment ion signals for parent and daughter short peptides. The identified amino acid enantiomers are used to form any possible short peptides by permutation and combination in an order from dipeptide to a tripeptide, to a tetrapeptide, and to even higher short peptides. The correct short peptides are confirmed by comparing the molecular weights of the constituent amino acid enantiomers and the molecular weights of identified short peptides together, with the characteristic N‐terminal peptide fragment ion signals. The amino acid sequence of the dipeptide ester aspartame and the tripeptide glutathione was successfully determined by this method. Abstract : A novel dual two‐dimensional HPLC online simultaneously couples to UV, FL, and ion‐trap MS has been developed for the amino acid sequence determination of two short peptides, Aspartame and Glutathione, using a bottom‐up strategy. The method can identify the amino acid isomers and enantiomers and does not need the use of database search.